Penilaian penempatan implan sebelum dan sesudah pemasangan implan gigi dengan pemeriksaan radiografi periapikal - Barunawaty Yunus; Dharmautama Dharmautama (Journal of Dentomaxillofacial Science, 2009)
The edentulous can be treated by many methods, in relevance to the more advancedtechnology in dentistry. Nowadays dental implant is more popular to replace the toothloss. This study was aimed to assess the implant placement before and after dentalimplant insertion through periapical radiographic examination. The subjects oftreatment consist of 30 implants which were inserted in aged of 20-50 years with onetooth loss, no history of sistemic disease with alveolar bone of 6 mm width and 10 mmheight. Analysis of distributed frequency and t-test showed the significant result ofimplant placement value before and after dental implant insertion through periapicalradiographic examination.